Appropriate indicated use for IVIG in neonatal infections - Wang, Ying; Ping Liu, Yi; Yan Yuan, Hai; Wen Xiao, Yi; Ping, Xu; Bo, Tao (Revista Cubana de Pediatría, 2016)
Infection is a leading cause of mortality and morbidity in the newborn and preterm neonates due to immuno-incompetence in these patients. Administration of intravenous immunoglobulin (IVIG) provides immunoglobulin G (IgG) that can protect the body from infection. In theory, morbidity and mortality due to infections in newborns and preterms infants could be reduced by the administration of IVIG. Two meta-analyses were evaluated comparing IVIG to treat various infection verses conventional treatments. The results showed IVIG is not effective as an adjunctive treatment for suspected or proven infections in neonates.